COVID-19: Main emergency assistance and safety measures for health professionals (Research, Society and Development, 2021)
This study aimed to identify in the scientific literature the main emergency assistance and safety measures for health professionals during the OVID-19 pandemic. It is an integrative literature review type research, from scientific publications indexed to the Scientific Electronic Library Online (SciELO), National Library of Medicine (PUBMED) and Academic Google databases, whose final sample was 21 articles. The main emergency assistance provided during the OVID-19 pandemic are the psychological, dental and surgical ones, which demonstrated a reduction in cases due to the safety measures adopted. In the search to minimize infections to health professionals and patients who are in hospital environments, safety measures were adopted, such as the use of IPE's according to the complexity of care and training for proper handling of these safety equipment. The present study demonstrated that the emergency assistance provided during the COVID-19 pandemic sought to offer safe care, aiming to safeguard the health of professionals who work in the front line, as well as patients.